THE FACTORS AFFECTING GREEN PRODUCTS PURCHASING BEHAVIOUR: A STUDY ON BANGLADESHI CUSTOMERS PERSPECTIVE - Taslim Ahammad; Bashir Uddin, Tania Islam, Dalilur Rahman (Journal of Islamic Management Studies, 2023)
The aim of this study is to examine the influence of green attitude, green advertisement and green product price on Bangladeshi green purchase behaviour. The study proposes a conceptual model, based on theory of planned behaviour (TPB). The theory is examining the relationship between attitude, subjective norms, perceived behavioural control and their impact on behaviour. Data was collected from 300 Bangladeshi customers. Structured questionnaires with purposive sampling method implemented to collect data mostly at famous shopping malls in Dhaka and Chittagong city area. The empirical finding of this research supported three out of three proposed hypotheses. The three dimensions that showed a positive and significant impact of green attitude, green advertisement and green product price on Bangladeshi green purchasing behaviour. Based on this research finding, the green attitude and green advertisement were the most influential factors impacting Bangladeshi green purchase behaviour. Theoretically the study supports the theory of planned behaviour proposes in which green advertisement considered as a subjective norm and green product price adopted as a planned behavioural control. The study has taken initiative for the future researcher and also marketers that they may conduct the result of this study for developing their marketing strategy in Bangladeshi context. The study will be a meaningful addition to the literature of the green attitude and green advertisement were the most influential factors impacting Bangladeshi green purchase behaviour. The finding also provides insight for knowledge seekers, by highlighting the Bangladeshi society green tendency and their green life style.